Analysis of Material and Form of French Listening Learning Questions Level A1 - Keisha Yumna Anindya; Yuliarti Mutiarsih; Farida Amalia (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The objectives of this study are as follows: 1) to analyze the listening comprehension materials and exercise types for A1-level French language learning on the francaisfacile.rfi.fr website; 2) to assess the alignment of the materials and exercise types with the Common European Framework of Reference for Languages (CEFR) standards for listening comprehension skills at A1 level; and 3) to identify the strengths and weaknesses of the listening materials and exercise types on the website as a learning medium. This study employed a qualitative descriptive approach. The data were obtained through literature review and documentation analysis, conducted online via the francaisfacile.rfi.fr website during the period of October-Desember 2025. The research population includes all A1-level French listening comprehension materials and exercises on the francaisfacile.rfi.fr website. Purposive sampling was used, focusing on A1-level listening materials and exercises. The research instruments consist of material analysis tables based on Bérard’s theory, a CEFR-based material alignment table adapted from Chauvet et al.’s theory, and an exercise types classification table based on Tagliante’s theory. The results show that the A1-level listening materials are divided into three main themes, namely Comprendre l’actualité en français, Réviser les points de langue, and Communiquer au quotidien. The exercise types were varied but predominantly consisted of single-correct-answer multiple-choice questions. The materials and exercises meet the CEFR level A1 standards. The website’s strengths lie in its comprehensive materials and authentic audio resources. However, it has limitations in terms of exercise variety, as well as the absence of communicative elements and teacher involvement. Therefore, the francaisfacile.rfi.fr website is considered suitable as a supplementary learning medium for A1-level French listening skills.